2017
DOI: 10.1038/emm.2017.183
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 promotes IL-10 production in macrophages: a role for IL-33 in macrophage foam cell formation

Abstract: We evaluated the role of IL-10- in IL-33-mediated cholesterol reduction in macrophage-derived foam cells (MFCs) and the mechanism by which IL-33 upregulates IL-10. Serum IL-33 and IL-10 levels in coronary artery disease patients were measured. The effects of IL-33 on intra-MFC cholesterol level, IL-10, ABCA1 and CD36 expression, ERK 1/2, Sp1, STAT3 and STAT4 activation, and IL-10 promoter activity were determined. Core sequences were identified using bioinformatic analysis and site-specific mutagenesis. The se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 30 publications
0
37
0
Order By: Relevance
“…The IL-33/ST2 complex thus suppresses IL-1β generation and the down-stream activation of the TLR signaling pathway by sequestration of MyD88 with the consequence of further inhibiting NF-kB and activating MAP kinases [46]. IL-33 indeed activates ERK1\2 and STAT3, facilitating binding of STAT3 to the − 1954 to − 1936 bp sequence upstream of the IL-10 transcription start site, thereby promoting its transcription in macrophages [47]. Although we did not analyze M1 and M2 monocytes in this study, previously published data indicate that M2 cells are significantly reduced in AD.…”
Section: Discussionmentioning
confidence: 99%
“…The IL-33/ST2 complex thus suppresses IL-1β generation and the down-stream activation of the TLR signaling pathway by sequestration of MyD88 with the consequence of further inhibiting NF-kB and activating MAP kinases [46]. IL-33 indeed activates ERK1\2 and STAT3, facilitating binding of STAT3 to the − 1954 to − 1936 bp sequence upstream of the IL-10 transcription start site, thereby promoting its transcription in macrophages [47]. Although we did not analyze M1 and M2 monocytes in this study, previously published data indicate that M2 cells are significantly reduced in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines are a large group of peptides and proteins, which are known to be involved in the signaling between the cells of the immune system [1, 2]. Examples of cytokines include interleukins (ILs), chemokines, interferons (IFNs), colony stimulating factors, tumour necrosis factors (TNFs), transforming growth factors (TGFs) and adipokines.…”
Section: Introductionmentioning
confidence: 99%
“…The requirement of the ST2 receptor in the anti-foam cell actions of IL-33 together with associated changes in gene expression was confirmed by the use of bone marrow-derived macrophages (BMDM) from mice deficient in this receptor 10 . Subsequent studies have also confirmed the requirement of the ST2 receptor in the IL-33-mediated regulation of expression of other genes in human macrophages together with its anti-foam cell action 11,13 . IL-33 also inhibited macropinocytosis 5 , which contributes to the disease via the macrophage uptake of LDL particles 1 .…”
Section: Introductionmentioning
confidence: 77%